Exploring national and international experiences with community first responder models: protocol for a scoping review - Hamidreza Khankeh; Abbas Naboureh; Mehrdad Farrokhi; Mohammad Saatchi; Shokoufeh Ahmadi; Fereydon Layeghi (BMJ Open, 2024)
Introduction Timely arrival of emergency medical services (EMS) is pivotal for effective prehospital care, and efforts by EMS leaders and policymakers to reduce response times, especially in cardiac arrests responsible for 70%–80% of coronary heart disease-related deaths, underscore the global urgency. With approximately 55 out-of-hospital cardiac arrests per 100 000 people annually, survival rates hinge on timely cardiopulmonary resuscitation, emphasising its initiation within a 4–6 min window. Trauma, causing 6 million deaths and nearly 40 million injuries a year, further underscores the need for prompt prehospital care. Acknowledging these challenges, health systems have incorporated community first responder (CFR) models, where trained community members provide initial aid, aiming to bridge the crucial gap until professional help arrives. This scoping review intends to explore the experiences of various countries with CFR models, including their conceptual and theoretical frameworks, recognising CFR as a critical solution for reducing response times in prehospital emergency care.Methods and analysis Arksey and O'Malley’s approach will be followed in this scoping review. Our protocol was drafted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols extension for Scoping Reviews. The study objective is to comprehensively understand and map current knowledge about CFR model characteristics and identify effective components and indicators. The review will encompass available articles indexed in PubMed, Scopus and Web of Science without restrictions on date of publication. Additional searches will explore grey literature on Google Scholar and reliable websites in the field of EMS. Articles published in languages other than English and those inaccessible in full text will not be considered for inclusion.Ethics and dissemination Since the study data are accessible from publicly accessible secondary sources, no ethical approval is necessary. Peer-reviewed publications will be used to report the study findings.